2011
DOI: 10.3801/iaffs.fss.10-307
|View full text |Cite
|
Sign up to set email alerts
|

Thermodynamic Analysis of Suppressant-Enhanced Overpressure in the FAA Aerosol Can Simulator

Abstract: The fire suppressant CF 3 Br has been banned for most applications but it is still used in come critical applications for which suitable replacements have not yet been found. One such application is the suppression of cargo-bay fires in aircraft. Recently, the agents C 2 HF 5 (pentafluoroethane, HFC-125), and bromotrifluoropropene (C 3 H 2 F 3 Br, 2-BTP) have been evaluated in a mandated Federal Aviation Administration (FAA) test, in which a simulated explosion of an aerosol can must be suppressed by the agent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 19 publications
0
6
0
Order By: Relevance
“…In the FAA-ACT, overpressures were observed (indicating an increase in flammability) [4,5]. Similarly, in a constantvolume apparatus at high agent loadings in lean flames, increases in pressure, burning velocity, and flame temperature were observed [23].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the FAA-ACT, overpressures were observed (indicating an increase in flammability) [4,5]. Similarly, in a constantvolume apparatus at high agent loadings in lean flames, increases in pressure, burning velocity, and flame temperature were observed [23].…”
Section: Discussionmentioning
confidence: 99%
“…Cup burner tests indicate that 2-BTP is an effective flame extinguisher at concentrations similar to those required by CF 3 Br [1][2][3]. However, it was unexpectedly found that when 2-BTP is added at subinerting concentrations in the U.S. Federal Aviation Authority Aerosol Can Test (FAA-ACT) [4][5][6][7][8] a large overpressure is obtained, causing the agent to fail the test and indicating that 2-BTP is reacting exothermically under these conditions. The development of a fundamental model explaining the chemical basis of these results would be of value to help assess the range of conditions where such behavior might be expected, as well as provide insights that could lead to the development of more effective agents.…”
Section: Introductionmentioning
confidence: 99%
“…The objective of this work was to develop a laboratory scale experiment to validate the theoretical work of Linteris (2011) andBabushok (2012) for aviation applications. The results of this work support their calculation model.…”
Section: Discussionmentioning
confidence: 99%
“…Theoretical research into the possible causes for these phenomena included development of calculation models to describe and predict the mechanisms of the specific explosion events (Linteris, 2011;Babushok, 2012). This provided some possible explanations about the chemistry involved.…”
Section: 1mentioning
confidence: 99%
“…8,9 Several studies have been performed to explain this phenomenon. 10–13 Perfectly stirred reactor simulations have indicated that adding the suppressant to the lean system increases the energy release rate and the overall reaction rate. 10 Thermodynamic equilibrium calculation indicated that the peak pressure rise occurred when the fuel and agent were completely consumed.…”
Section: Introductionmentioning
confidence: 99%